Direct conjugation with a zero length linker of fullerene C70 to ZnO quantum dots for multicolor light-emitting diodes. Issue 6 (1st May 2020) - Park, Young Jae; Shim, Jaeho; Lee, Kyu Seung; Lee, Won Ki; Hwang, Jun Yeon; Lee, Hyunbok; Yi, Yeonjin; Angadi, Basavaraj; Choi, Won Kook; Son, Dong Ick
Abstract : Our work demonstrates whitish light-emitting diodes by fullerene induced multicolor emission from environmentally friendly ZnO-fullerene C70 quantum dots that is synthesized by simple and facile chemical reaction with zero length linker. Abstract : Environmentally friendly metal oxide quantum dot (QD) nanostructures have become attractive alternative materials for replacing QDs containing toxic elements of Cd and Pb. Although many attempts have been proposed for optoelectronic applications of hybrid metal oxide QDs with tailored opto-electronic properties, the fabrication of heterogeneous QD–fullerene hybrids as an emissive material has been studied little for optoelectronic devices. Herein, we report the preparation of ZnO–fullerene C70 (ZnO–C70 ) QDs by a facile chemical reaction with a zero length linker and demonstrate whitish light-emitting diodes by fullerene induced multicolor emission from the ZnO–C70 QD heterostructure. The electroluminescence (EL) is attributed to three new emission features in the visible region that originate from the electron transitions from three split lowest unoccupied molecular orbital levels of C70 molecules to the valence band of ZnO QDs. Compared with photoluminescence, the EL emission was red-shifted by 50–130 meV due to the interaction between ZnO–C70 QDs in the solid state. The energy levels of C70 were also suitably aligned to those of ZnO QDs with a lower electron transfer barrier of 0.22 eV, which offers an advantageous route for electron transport. Consequently, the environmentally friendly ZnO–C70 QDs with extraordinary properties promise great potential for use as novel encapsulating materials in the field of opto-electronic applications adopting QDs.